A facile synthesis of 3β, 25-dihydroxy-5α-cholest-7-ene, the precursor to HMG-CoA reductase inhibitor. (1st March 2018) - Jin, Can; Liao, Zhibing; Sun, Bin; Xu, Tengwei
An efficient four-step procedure is described for the synthesis of 3β, 25-dihydroxy-5α-cholest-7-ene from 3β-hydroxy-5α-cholesta-7, 24-diene in an overall yield of 34%. This product can serve as a precursor for the synthesis of an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase. The 3β-toluene-p-sulfonate ester of 5α-cholesta-7, 24-diene was obtained from natural lanolin followed by treatment with toluene-p-sulfonyl chloride. The key step in the synthesis is a very mild method for the hydroxybromination of this ester with N-bromosuccinimide in water, followed by reduction with LiAlH4 to obtain the 3β-toluene-p-sulfonate ester of 25-hydroxy-5α-cholesta-7-ene. The final product was obtained after desulfonation of 3β-toluene-p-sulfonyoxy-25-hydroxy-5α-cholesta-7-ene to afford 3β, 25-dihydroxy-5α-cholest-7-ene in excellent yield. The reagents are all relatively cheap, non-toxic and stable.